At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

HELP!!! MATH!!! 100 PTS !!!

Suppose f is a one-to-one, differentiable function and its inverse function f−1 is also differentiable. One can show, using implicit differentiation (do it!), that
(f^−1)′(x)=1/(f′(f^−1(x)))
Find (f^−1)′(6) if f(−1)=6 and f′(−1)=3/7.


Sagot :

Answer:

(f^−1)′(6)=1/(f'(f^-1(6)))

(f^−1)′(6)=1/(f'(f^-6)))

I hope this helps.